Formation of Ni(ii)-phenoxyl radical complexes by O2: a mechanistic insight into the reaction of Ni(ii)-phenol complexes with O2. Issue 15 (19th March 2021) - Suzuki, Takashi; Sato, Akari; Oshita, Hiromi; Yajima, Tatsuo; Tani, Fumito; Abe, Hitoshi; Mieda-Higa, Kaoru; Yanagisawa, Sachiko; Ogura, Takashi; Shimazaki, Yuichi
Abstract : The reaction of Ni(ii )-(phenol)(phenolate) complexes with O2 gave the Ni(ii )-phenoxyl radical complexes assisted by CH3 OH. This reaction was concluded to undergo via the proton transfer–electron transfer type mechanism without redox of the Ni ion. Abstract : A reaction of Ni(ClO4 )2 ·6H2 O with a tripodal ligand having two di( tert -butyl)phenol moieties, H2 tbuL, and 1 equivalent of triethylamine in CH2 Cl2 /CH3 OH (1 : 1, v/v) under N2 gave a Ni II -(phenol)(phenolate) complex, [Ni(HtbuL)(CH3 OH)2 ]ClO4 . The formation of the Ni II -phenoxyl radical complex by O2 was observed in the reaction of this complex in the solid state. On the other hand, the Ni II -phenoxyl radical complex [Ni(Me2 NL)(CH3 OH)2 ]ClO4 was obtained by the reaction of H2 Me2 NL having a p -(dimethylamino)phenol moiety with Ni(ClO4 )2 ·6H2 O in a similar procedure under O2, through the oxidation of the Ni II -(phenol)(phenolate) complex. However, a direct redox reaction of the Ni II ion could not be detected in the phenoxyl radical formation. The results of the reaction kinetics, XAS and X-ray structure analyses suggested that the O2 oxidation from the Ni II -(phenol)(phenolate) complex to the Ni II -phenoxyl radical complex occurs via the proton transfer–electron transfer (PT–ET) type mechanism of the phenol moiety weakly coordinated to the nickel ion.